Respuesta :
Answer:
Divide each term by 7 and simplify.
cā12=ā3
Move all terms not containing c to the right side of the equation.
c=9
Step-by-step explanation:
C = 9
Step by step:
7(c - 12) = -21
We divide both sides of the equation by 7
C - 12 = -3
The we move the constant, - 12, to the right hand side and change its sign.
C = -3 + 12
Then we calculate the sum
C = 9
Step by step:
7(c - 12) = -21
We divide both sides of the equation by 7
C - 12 = -3
The we move the constant, - 12, to the right hand side and change its sign.
C = -3 + 12
Then we calculate the sum
C = 9